Exploratory study on good practices for innovation in a group of small and medium-sized enterprises (SMes) in Boyaca (2019)
This article shows results of the research done in boyacá by the Universidad Pedagógica y Tecnológica de Colombia named Innovation Data, Indicators, Information and Knowledge in Colombia, which was expanded to diverse regions of the country by the Universities Eafit, Surcolombiana and Tecnológica de bolívar. This text also presents the good innovation practices in a representative group of SMEs, which were classified as producers of goods and services, and belonged to the industrial (agroindustry, manufacturing and textiles) and service (tourism, IT, health and transportation) sectors in boyacá, especially in the cities of Tunja, Paipa, Duitama and Sogamoso. The innovation valuation was made based on entrepreneur self-assessment of their products, services, processes, management and market. The results indicate that the SMEs group is considered to be in a stage of development, and that present relevant gaps in the four types of innovation.